1993
DOI: 10.1083/jcb.121.6.1385
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways for sphingosylphosphorylcholine-mediated mitogenesis in Swiss 3T3 fibroblasts.

Abstract: Abstract. Sphingosylphosphorylcholine (SPC), or lysophingomyelin, a wide-spectrum growth promoting agent for a variety of cell types (Desai, N. N., and S. Spiegel. 1991. Biochem. Biophys. Res. Comm. 181: 361-366), stimulates cellular proliferation of quiescent Swiss 3T3 fibroblasts to a greater extent than other known growth factors or than the structurally related molecules, sphingosine and sphingosine-l-phosphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 61 publications
(124 reference statements)
4
79
1
Order By: Relevance
“…To confirm its LPA-like effects, SPC was applied to oocytes that were voltage-clamped at Ϫ60 mV, and membrane currents were recorded. The SPC preparation obtained from Sigma, which is used by many of the investigators who reported its LPA-like effects (6,11,16,17,(33)(34)(35)(36), elicited oscillatory currents with a threshold concentration in the low micromolar range (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm its LPA-like effects, SPC was applied to oocytes that were voltage-clamped at Ϫ60 mV, and membrane currents were recorded. The SPC preparation obtained from Sigma, which is used by many of the investigators who reported its LPA-like effects (6,11,16,17,(33)(34)(35)(36), elicited oscillatory currents with a threshold concentration in the low micromolar range (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Electrophysiological Recording from Xenopus Oocytes-Oocytes were obtained from xylazine-anesthetized adult Xenopus laevis frogs (Carolina Scientific, Burlington, NC) under aseptic conditions and were prepared for experiments as described previously (33). Lipids for bioassay were always complexed with fatty acid-free BSA (Sigma, for complexing procedure see below), diluted in frog Na ϩ -Ringer's solution (120 mM NaCl, 2 mM KCl, 1.8 mM CaCl 2 , 5 mM HEPES, pH 7.0), and were applied through superfusion to the oocyte, at a flow-rate of 5 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…A metabolite of the membrane lipid sphingomyelin, sphingosine (SP), has previously been shown to be a potent inhibitor of PKC, and it has been suggested that SP may be an endogenous inhibitor of PKC in cells [11,12]. Furthermore, SP and its derivatives have been shown to activate the release of sequestered Ca2+ [13][14][15][16][17]. In addition, SPs have been implicated as potent inhibitors of calmodulin-dependent enzymes [18], an interesting observation considering that calmodulin may be of importance in regulating Ca2+ fluxes in FRTL-5 cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…SP derivatives are also potent mitogenic agents, and the mitogenicity may be linked to the formation of arachidonic acid [14,15]. Arachidonic acid and its metabolites may be important in the regulation of Ca2+ entry in FRTL-5 cells [20], and may be of significance in regulating the proliferation of FRTL-5 cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…and to stimulate PKC activity [8]. Thus, SphPCho activated two important signal-transduction pathways involved in the regula-…”
mentioning
confidence: 99%